Novel Molecule Nell-1 Promotes the Angiogenic Differentiation of Dental Pulp Stem Cells - Li, Mengyue; Wang, Qiang; Han, Qi; Wu, Jiameng; Zhu, Hongfan; Fang, Yixuan; Bi, Xiuting; Chen, Yue; Yao, Chao; Wang, Xiaoying (Frontiers in Physiology, 2021)
Introduction This work aimed to reveal the crucial role of Nell-1 in the angiogenic differentiation of human dental pulp stem cells (DPSCs) alone or co-cultured with human umbilical vein endothelial cell (HUVECs) in vitro and whether this molecule is involved in the pulp exposure model in vivo. Methods Immunofluorescence was conducted to ascertain the location of Nell-1 on DPSCs, HUVECs, and normal rat dental tissues. RT-PCR, Western blot, and ELISA were performed to observe the expression levels of angiogenic markers and determine the angiogenic differentiation of Nell-1 on DPSCs alone or co-cultured with HUVECs, as well as in vitro tube formation assay. Blood vessel number for all groups was observed and compared using immunohistochemistry by establishing a rat pulp exposure model. Results Nell-1 is highly expressed in the nucleus of DPSCs and HUVECs and is co-expressed with angiogenic markers in normal rat pulp tissues. Hence, Nell-1 can promote the angiogenic marker expression in DPSCs alone and co-cultured with other cells and can enhance angiogenesis in vitro as well as in the pulp exposure model. Conclusion Nell-1 may play a positive role in the angiogenic differentiation of DPSCs.